Rancang Rancangan Sistem Akuntansi Gudang PT Kao Indonesia Chemical Karawang - Komalasari, Yuli (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
PT Kao Indonesia, which was founded in 1985, is engaged in the manufacture of consumer goods with a focus on health, beauty and care products, focusing on the production and sale of products such as detergents, sanitary napkins, body and facial cleansers. consumer. Kao's production sites are in Jababeka – Cikarang for production and KIIC Karawang for the Logistic Center. Inventory of goods or stock is important for companies, both trading companies or factories that carry out production. In order for sales to make a profit, a well-planned inventory is needed. Incorrect recording in inventory can result in company losses in the accounting period. Inventory consists of goods to be processed, goods to be produced, and finished goods. Inventory accounting information system has not been computerized properly. With the Warehouse Accounting system that is integrated with the Marketing, Production and Purchasing sections, Inventory planning is well maintained, so that stock can be maintained, not excessive and not lacking when going into production. Payment schedules to suppliers can be scheduled properly, and payment information from customers is also expected to be better. Keywords : Consumer Good, Warehouse Accounting System, Integrated